Chromosome-Level Alpaca Reference Genome VicPac3.1 Improves Genomic Insight Into the Biology of New World Camelids - Richardson, Mark F.; Munyard, Kylie; Croft, Larry J.; Allnutt, Theodore R.; Jackling, Felicity; Alshanbari, Fahad; Jevit, Matthew; Wright, Gus A.; Cransberg, Rhys; Tibary, Ahmed; Perelman, Polina; Appleton, Belinda; et al. (Frontiers in Genetics, 2019)
The development of high-quality chromosomally assigned reference genomes constitutes a key feature for understanding genome architecture of a species and is critical for the discovery of the genetic blueprints of traits of biological significance. South American camelids serve people in extreme environments and are important fiber and companion animals worldwide. Despite this, the alpaca reference genome lags far behind those available for other domestic species. Here we produced a chromosome-level improved reference assembly for the alpaca genome using the DNA of the same female Huacaya alpaca as in previous assemblies. We generated 190X Illumina short-read, 8X Pacific Biosciences long-read and 60X Dovetail Chicago® chromatin interaction scaffolding data for the assembly, used testis and skin RNAseq data for annotation, and cytogenetic map data for chromosomal assignments. The new assembly VicPac3.1 contains 90% of the alpaca genome in just 103 scaffolds and 76% of all scaffolds are mapped to the 36 pairs of the alpaca autosomes and the X chromosome. Preliminary annotation of the assembly predicted 22,462 coding genes and 29,337 isoforms. Comparative analysis of selected regions of the alpaca genome, such as the major histocompatibility complex, the region involved in the Minute Chromosome Syndrome and candidate genes for high-altitude adaptations, reveal unique features of the alpaca genome. The alpaca reference genome VicPac3.1 presents a significant improvement in completeness, contiguity and accuracy over VicPac2 and is an important tool for the advancement of genomics research in all New World camelids.